A Host of Contradictions: State Compulsion and the Educational Experience of Soviet Russia's Youth, 1931–1945. Issue 3 (2nd July 2020) - Holmes, Larry E.
Abstract: Based on oral and written testimony of pupils and teachers, this essay examines the lived educational experience of the school-age cohort of children in Stalin's Russia from 1931 to 1945. The state alone determined the structure and curricula of the nation's schools. However, Soviet youngsters, their parents, and teachers responded to the center's initiatives in ways that both embraced and defied the attempt to make anew society and humans. They thereby at once hindered, shaped, and advanced the state's schemes to use the school as an instrument for the creation of a Soviet variant of modernity.